A rare association of Down syndrome with Dandy eWalker variant, pulmonary hypertension and childhood interstitial lung disease: A case report of a prognostic dilemma - Mohd Kori, Anis Munirah; Alias, Amelia; Daud, Mariana; Yahaya, Nor Azni; Anuar, Muhamad Azamin (Elsevier, 2022)
Associations among Down syndrome (DS), Dandy eWalker variant (DWv), pulmonary hypertension (PH) and childhood interstitial lung disease (chILD) are extremely rare. Several cases of trisomy disorders with DandyeWalker malformation (DWM) and neurodevelopmental outcomes have been reported. The extent to which moderate to severe pulmonary hypertension with complications of patent ductus arteriosus (PDA), PH and chILD leads to substantial morbidity and mortality in infants with DS and DWM should be studied. We report the case of an ex-premature 15-month-old girl with confirmed DS with DWv, who developed PH and chILD. This is the first case study reporting the complexity of multiple associations involving DS and DWv. This case led to a prognostic dilemma and required compassionate parental counselling because of the child’s uncertain future.